Recycling of Plastic Waste: How the Conditions of Thermal Cracking and the Composition of Plastic Mixtures Affect Product Yield; Recycling; Vol. 11, iss. 2 - Frolova U. A. Uljyana Aleksandrovna; Urazov Kh. Kh. Khoshim Khoshimovich; Sviridenko N. N. Nikita Nikolaevich; Kolobova E. N. Ekaterina Nikolaevna (2026, 2026)
Title screen